Effect of Axial Loading on the Arches of the Foot in Varying Age Groups (International Journal of Physiotherapy, 2026)
Background: The arches of the foot, particularly the Medial longitudinal arch is crucial for supporting body weight and absorbing shock. Axial loading, or vertical weight-bearing, impacts foot arch structure differently across age groups. This study investigates the effect of axial loading on foot arches across different age groups using the Arch Index (AI) and the Feiss Line assessment.Methods: This observational study included 84 participants (49 Female and 35 Male) categorized into four age groups (10-16, 17-30, 31-45, and>45 years). Arch structure was analyzed using ink-based footprint methods and the Feiss Line test under weight-bearing conditions. Arch Index values were calculated, and Feiss line grading was recorded for both feet. Data analysis involved applying ANOVA and Chi-square tests to compare group outcomes.Results: Notable variations in Arch Index values were observed between age groups in both right (p= 0.023) and left foot (p= 0.014). Older adults (>45 years) exhibited the flattest arches. Age- related differences in Feiss Line grading were statistically significant in the right foot (p=0.038), but not in the left (p > 0.05).Conclusion: Aging is associated with progressive flattening of the arch under axial loading. Routine foot screening and early interventions are recommended to maintain foot biomechanics across the lifespan.